2013
DOI: 10.1080/2153599x.2012.736714
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive resource depletion in religious interactions

Abstract: We explore the cognitive effects of three common features of religious interactions: (1) demand for the expressive suppression of emotion; (2) exposure to goaldemoted and causally opaque actions; and (3) the presence of a charismatic authority. Using a cognitive resource model of executive function, we argue that these three features affect the executive system in ways that limit the capacity for individual processing of religious events. We frame our analysis in the context of a general assumption that collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 113 publications
(99 reference statements)
7
108
1
3
Order By: Relevance
“…In a 2013 target article in Religion, Brain & Behavior, Schjoedt and colleagues explored the ways in which religious interactions tend to deplete cognitive resources. They proposed a "resource model of ritual cognition in which collective rituals limit the cognitive resources available for the individual processing of religious events", and demonstrated the way in which "rituals directly suppress and channel default cognition in order to facilitate the construction of collective memories, meanings, and values among ritual participants" ( [49], p. 40). Rituals tend to be characterized by incomprehensible-or at least causally opaque-interactions.…”
Section: The Reciprocity Of God-bearing Biasesmentioning
confidence: 99%
“…In a 2013 target article in Religion, Brain & Behavior, Schjoedt and colleagues explored the ways in which religious interactions tend to deplete cognitive resources. They proposed a "resource model of ritual cognition in which collective rituals limit the cognitive resources available for the individual processing of religious events", and demonstrated the way in which "rituals directly suppress and channel default cognition in order to facilitate the construction of collective memories, meanings, and values among ritual participants" ( [49], p. 40). Rituals tend to be characterized by incomprehensible-or at least causally opaque-interactions.…”
Section: The Reciprocity Of God-bearing Biasesmentioning
confidence: 99%
“…Following the basic principle of Helmholtz that perception is active inference, many studies have shown how sensory signals are "explained away" by top-down predictive signals, while bottom-up prediction errors result in the updating of the prior model. While predictive processing has been successfully applied to explain basic perception, recently the framework has been extended to more complex phenomena as well, such as delusional beliefs (Fletcher & Frith, 2009), religious experience (Taves & Asperem, 2016), and religious rituals (Schjoedt et al, 2013). Central to these theoretical accounts is that religious beliefs are acquired and maintained through a process of reduced prediction error monitoring.…”
Section: Bayes In the Brain: Theoretical Innovationmentioning
confidence: 99%
“…An increased reliance on religious authority results in a reduced process of error monitoring and a failure to update one's model based on the available evidence. Recently it has been argued that religious rituals are specifically aimed at reducing the process of error monitoring, thereby enhancing people's willingness to uncritically adopt a prevailing worldview (Schjoedt et al 2013). In line with this suggestion, it has been found for instance that believers are characterized by a reduced activation of the frontal executive monitoring network when listening to a religious authority (Schjoedt et al 2011).…”
Section: Context and Model Adjustmentmentioning
confidence: 99%